Priority setting for health in the context of devolution in Kenya: Implications for health equity and community-based primary care - McCollum, R; Theobald, S; Otiso, L; Martineau, T; Karuga, R; Barasa, E; Molyneux, C; Taegtmeyer, M (Oxford University Press, 2018)
Devolution changes the locus of power within a country from central to sub-national levels. In 2013, Kenya devolved health and other services from central government to 47 new sub-national governments (known as counties). This transition seeks to strengthen democracy and accountability, increase community participation, improve efficiency and reduce inequities. With changing responsibilities and power following devolution reforms, comes the need for priority-setting at the new county level. Priority-setting arises as a consequence of the needs and demand for healthcare resources exceeding the resources available, resulting in the need for some means of choosing between competing demands. We sought to explore the impact of devolution on priority-setting for health equity and community health services. We conducted key informant and in-depth interviews with health policymakers, health providers and politicians from 10 counties (n = 269 individuals) and 14 focus group discussions with community members based in 2 counties (n = 146 individuals). Qualitative data were analysed using the framework approach. We found Kenya's devolution reforms were driven by the need to demonstrate responsiveness to county contexts, with positive ramifications for health equity in previously neglected counties. The rapidity of the process, however, combined with limited technical capacity and guidance has meant that decision-making and prioritization have been captured and distorted for political and power interests. Less visible community health services that focus on health promotion, disease prevention and referral have been neglected within the prioritization process in favour of more tangible curative health services. The rapid transition in power carries a degree of risk of not meeting stated objectives. As Kenya moves forward, decision-makers need to address the community health gap and lay down institutional structures, processes and norms which promote health equity for all Kenyans.